The origin of ultrapotassic igneous rocks - Foley, Stephen F(Stephen Francis) (1986)
This thesis consists of a review of ultrapotassic igneous rock occurrences and three experimental programs designed to examine the petrogenesis of the lamproites. A definition for ultrapotassic rocks is introduced using the whole-rock chemical screens K20>3 wt%, MgO>3 wt% and K20/Na20>2. Three major end-member groups are recognised; Group I (lamproites) are characterised by low CaO, A1203 and Na 2 0, high K 2 0/A1203 and Mg-number, and extremely high incompatible element contents; Group II have low Si0 2 and high CaO, and lower incompatible elements than group I although they have high relatively Sr; Group III rocks occur in orogenic areas and have high CaO and A1203, and low Ti0 2 , Nb and Ba typical of island arc rocks. Primary magmas-for all three groups probably originate by partial melting of mantle material enriched in incompatible elements. The chemical signatures of the groups indicate differences in (i) source composition prior to enrichment, (ii) the chemical nature of the enriching agent, and (iii) pressure-temperature conditions of melting. The liquldus mineralogy of a pristine, primary leucite lamproite from-- Gaussberg, Antarctica, was studied at .1 atm with controlled f0 2 , oxygen fugacity at the time of crystallisation of the Gaussberg rock is shown by ferric value [10OFe 3 /(Fe 3 +Fe2 )] of spinel, Fe 2 03 content of leucite and Mg-number of olivine, to have been just below NNO. Application of the spinel ferric value calibration to other lamproites indicates that they began to crystallise at f0 2 ranging from MW to above NNO. The ferric value of spinel is very sensitive to changes in oxygen fugacity, and may prove useful as a diamond survivability indicator': diamonds are unlikely to survive in the more oxidised lamproite magmas. The effect of fluorine, an important constituent of ultrapotassic rocks, on phase relationships in the kalsilite-forsterite-quartz system was studied at 28kbar. Fluorphiogopite is found to be stable to 300 0C higher than hydroxyphlogopite, and the peritectic ...